Voltage Stress Reduction on Compensation Capacitors of Wireless Charging Systems for Transport and Industrial Infrastructure - Pavelek, Miroslav; Spanik, Pavol; Frivaldsky, Michal (Communications - Scientific letters of the University of Zilina, 2019)
The paper deals with a proposal for circuit configuration of series-series (SS) compensated wireless power transfer (WPT) system with reduced voltage stresses on compensation capacitors. Nowadays, a huge effort is given for the development of reliable, efficient and robust wireless charging systems and therefore the circuit configuration and component selection are crucial to meet suitable operational characteristics. For this purpose, the current trends in WPT systems are outlined in the first section. Next, the analysis of frequently utilized WPT system configuration is provided and the most critical issues related to practical utilization are discussed. Consequently, the proposal of how to eliminate negative aspects is given. All theoretical statements are supported by mathematical apparatus of the proposed system and consequently by the simulation analysis.